The Marulu Strategy 2008-2012: overcoming Fetal Alcohol Spectrum Disorder (FASD) in the Fitzroy Valley - James P. Fitzpatrick; June Oscar; Maureen Carter; Elizabeth J. Elliott; Jane Latimer; Edie Wright; John Boulton (Elsevier, 2017)
Abstract Objective: Aboriginal leaders concerned about high rates of Fetal Alcohol Spectrum Disorder (FASD) in the Fitzroy Valley, remote north‐western Australia, introduced restrictions on access to take‐away full‐strength alcohol. Following this, Aboriginal leaders engaged strategic partners in a broader strategy to address FASD in the region. The aim of this study was to develop and implement a community‐led, researcher‐supported, FASD strategy. Methods: A review of literature focusing on community‐led FASD strategies identified key components that informed the Marulu FASD strategy. These included strategy ownership, leadership, and governance by participating communities, and a research framework. Results: Community meetings and workshops led to the development of The Marulu FASD Strategy (2008). Feasibility and community consent to conduct a FASD prevalence study (the Lililwan Project) was confirmed, and implementation was progressed (2010-2013). Concurrent FASD prevention activities were conducted. In 2012, the Marulu FASD Unit was established within a local Aboriginal organisation to sustain and coordinate ongoing strategy activities. Conclusions: Community control of public health initiatives can be achieved when Aboriginal communities prioritise issues of significant concern, and engage strategic partners to overcome them. Implications for public health: The Marulu Strategy forms a template for action to address FASD and other public health issues in Aboriginal communities in Australia and internationally.